2020
DOI: 10.1007/s40979-020-00058-2
|View full text |Cite
|
Sign up to set email alerts
|

Academic integrity and the implementation of the honour code in the clinical training of undergraduate dental students

Abstract: Educational pressures such as challenging workload, demanding deadlines and competitiveness among undergraduate dental students erode academic integrity in clinical training. The implementation of honour codes have been associated with the reduction in academic dishonesty. An action research was undertaken to investigate and foster academic integrity through creative pedagogical strategies and the implementation of an honour code within the undergraduate dental programme. Students r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…While, in comparison to this, cheating is less in those educational institutions where there are strong honor codes for academic cheating. The research has suggested that strong honor codes have a positive role in controlling academic cheating, and through honor codes, academic cheating can be decreased (Raman & Ramlogan, 2020). The other findings show that students also cheat more when the assigned work to them is boring or inappropriate.…”
Section: Motivational Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…While, in comparison to this, cheating is less in those educational institutions where there are strong honor codes for academic cheating. The research has suggested that strong honor codes have a positive role in controlling academic cheating, and through honor codes, academic cheating can be decreased (Raman & Ramlogan, 2020). The other findings show that students also cheat more when the assigned work to them is boring or inappropriate.…”
Section: Motivational Factorsmentioning
confidence: 98%
“…We need to focus on changing the values and attitudes of students so that they refrain from cheating. If the above-recommended actions are not taken, cheating will be considered favorable and probably be powerful until grades decide how good a student is and predict the future success of a student (Raman & Ramlogan, 2020).…”
Section: Recommendationsmentioning
confidence: 99%
“…The fundamental value of academic integrity ICAI (2021) identified five core values as the basis for its definition of academic integrity -honesty, trust, fairness, respect, and responsibility (Figure 4). The sixth value of courage has been added as a quality element of adherence to the five core values even in the face of difficulty (Raman & Ramlogan, 2020). Macfarlane (2014) described academic integrity as the values, behavior, and conduct of academics in all aspects of their practice.…”
Section: 31mentioning
confidence: 99%
“…There has also been no shortage of advice from administrators and faculty on ways educational institutions can improve their culture of academic integrity (e.g., Christensen Hughes & McCabe, 2006b;McCabe et al, 2012;Morris, 2018;Whitley & Keith-Spiegel, 2002). To put it bluntly, some percentage of students violate academic integrity, many faculty and administrators complain that they do, and at various points in an institution's history-often in response to a cheating scandal or a growing unease that the situation has gotten out of hand-faculty and administration introduce new programs, policies and/or pedagogical innovations designed to improve academic integrity (e.g., Raman & Ramlogan, 2020).…”
Section: Introductionmentioning
confidence: 99%